(untitled) (Global Journal of Management and Business Research, 2016)
Mentorship is a critical leadership development activity. Our study merges previous work on mentoring attributes and behaviors with an understanding of life-career seasons: the idea that as we progress through our careers and our lives, our mentoring needs change. Using an analysis of survey data from 1,836 US Army officers at different ranks, we find that life-career stages mediate the preferences of protégés for different mentoring functions. As theory predicts, we find that early careerists emphasize career development and job coaching mentoring functions, while later careerists place more value on personal development. These findings should inform how mentors should adjust their mentoring style and emphasis depending on the protégé’s life-career stage.